Changes of Serum Homocysteine and Vitamin B12, but Not Folate Are Correlated With Obsessive-Compulsive Disorder: A Systematic Review and Meta-Analysis of Case-Control Studies - Yan, Sirui; Liu, Hailong; Yu, Yaqiong; Han, Nashu; Du, Wenzhi (Frontiers in Psychiatry, 2022)
Background Obsessive–compulsive disorder (OCD) a complex neuropsychiatric disorder, is characterized by irresistible obsessive thinking and compulsive behavior. Folate is a member of water-soluble vitamins in the human body and sustains many normal daily activities (e.g., exercise, sleep, and memory). Homocysteine, a sulfur-containing non-essential amino acid, has been investigated in numerous psychiatric disorders (e.g., OCD). Vitamin B12 is a type of complex organic compound with cobalt contained. Moreover, vitamin B12 and folate deficiency and high levels of homocysteine were found to have an effect on brain functions and also lead to non-specific psychiatric symptoms. Objectives This study aimed to confirm the epidemiological evidence of OCD and investigate whether vitamin B12, folate, and homocysteine have an effect on the etiology of OCD. Methods A systematic search was conducted on eight databases (i.e., PubMed, Embase, Web of Science, the Cochrane Library, China Biology Medicine disc, China National Knowledge Infrastructure, Wanfang Database, China Science and Technology Journal Database), and the retrieval time was up to March 2021. The available articles involving patients with OCD with/without abnormal serum levels of vitamin B12, folate, and homocysteine were comprehensively reviewed and analyzed. Results A total of 5 studies involving 309 patients were included in this meta-analysis, including 172 cases in the experimental group and 137 in the control group. The content of folate in the OCD group was not significantly different from that in the control group (SMD = −0.089, 95%CI −0.755 to 0.577, p = 0.794). And serum homocysteine was significantly higher in the patients with OCD (SMD = 1.132, 95%CI 0.486 to 1.778, p = 0.001). Vitamin B12 was significantly lower in patients with OCD (SMD = −0.583, 95%CI −0.938 to −0.229, p = 0.001). Conclusions This meta-analysis shows serum high levels of homocysteine, low levels of vitamin B12, and normal folate level are closely correlated with OCD. However, high-quality case-control studies should be further conducted to explore the correlation between serum levels of vitamin B12, folate, homocysteine, and OCD. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021262161; PROSPERO (Number CRD#42021262161).